2020
DOI: 10.1038/s41467-020-17060-4
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of the tumour-associated EMP3 enhances erythroid proliferation and causes the MAM-negative phenotype

Abstract: The clinically important MAM blood group antigen is present on haematopoietic cells of all humans except rare MAM-negative individuals. Its molecular basis is unknown. By whole-exome sequencing we identify EMP3 , encoding epithelial membrane protein 3 (EMP3), as a candidate gene, then demonstrate inactivating mutations in ten known MAM-negative individuals. We show that EMP3, a purported tumour suppressor in various solid tumours, is expressed in erythroid cells. Disruption of EMP3 by CR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 33 publications
0
18
0
Order By: Relevance
“…Enucleation capacity of BEL-A was further improved by subsequent adjustment of the differentiation protocol to give a rate of $40%. 10 The unlimited proliferative window and ease of molecular manipulation, combined with unparalleled enucleation capacity, have enabled the application of BEL-A for demonstrating proof-ofprinciple production of reticulocytes with increased transfusion compatibility, 11 identifying the molecular basis of the MAM blood group antigen, 12 and the study of surface protein requirements for Plasmodium falciparum invasion. 13 However, isolation of BM CD34 + cells is highly invasive, so the ability to generate lines from more accessible PB and CB CD34 + cells is essential for opening up wider applications of the technology, such as creating lines from individuals with specific and rare blood group phenotypes and from patients with erythroid diseases for research purposes.…”
Section: Introductionmentioning
confidence: 99%
“…Enucleation capacity of BEL-A was further improved by subsequent adjustment of the differentiation protocol to give a rate of $40%. 10 The unlimited proliferative window and ease of molecular manipulation, combined with unparalleled enucleation capacity, have enabled the application of BEL-A for demonstrating proof-ofprinciple production of reticulocytes with increased transfusion compatibility, 11 identifying the molecular basis of the MAM blood group antigen, 12 and the study of surface protein requirements for Plasmodium falciparum invasion. 13 However, isolation of BM CD34 + cells is highly invasive, so the ability to generate lines from more accessible PB and CB CD34 + cells is essential for opening up wider applications of the technology, such as creating lines from individuals with specific and rare blood group phenotypes and from patients with erythroid diseases for research purposes.…”
Section: Introductionmentioning
confidence: 99%
“…EMP3 belongs to the peripheral myelin protein 22 (PMP22)/claudin superfamily of proteins and has four transmembrane domains. 15 , 16 Aberrant expression of EMP3 has been found in many cancers. Recently, many studies have focused on the role of EMP3 in tumor progression and malignant transformation.…”
Section: Introductionmentioning
confidence: 99%
“…Some previously published studies have found that PTPRC, as a kind of PTP family, could regulate the T-and B-cell antigen receptor signaling (15,16). EMP3 regulates cell growth and cell-cell interaction, and might function as a tumor suppressor in some cancers (30,31). MAPK7 as an important member of the MAPK family, and could act as a mediator for some downstream signaling pathways that are involved in a number of cellular activities, including proliferation, differentiation, transcription regulation, and development (32).…”
Section: Discussionmentioning
confidence: 99%